Hubungan Status Ekonomi dan Usia terhadap Anemia pada Ibu Hamil di Puskesmas Putri Ayu Kota Jambi - Irawan, Lucia (Indonesian Journal of Health Community, 2024)
Anemia can damage the blood's capacity to transport oxygen throughout the body. The purpose of this study was to determine the relationship between economic status and age towards anemia in pregnant women. The research method used is analytic with a retrospective approach with a population of all pregnant women who carry out HB checks at the Puskesmas Putri Ayu Kota Jambi in 2022, namely 831 samples. Sampling used a random sampling technique of 83 samples. The results of the study revealed there were 40 respondents (48.2%) of poor economic status and 46 people or 55.4% of age who were at risk of anemia. After being analyzed using the chi-square statistical test, it turned out that there was a relationship between economic status and anemia in pregnant women with a value of p = value = 0.000 (p <0.05) and an Odd Ratio (OR) of 799,500. This also shows that there is a significant relationship between maternal age and the incidence of anemia in pregnant women at the Putri Ayu Health Center, with an OR of 5,580. From the results of this study it is hoped that health workers will improve health services and health education for pregnant women.